The future of imprisonment - Tonry, Michael H. (Oxford Univ. Press, 2004)
1. Has the prison a future? / Michael Tonry -- 2. Crime, law, and the community: dynamics of incarceration in New York City / Jeffrey Fagan -- 3. Restoring rationality in punishment policy / Alfred Blumstein -- 4. Limiting retributivism / Richard S. Frase -- 5. Sentencing reform "reform" through sentencing information systems / Marc L. Miller -- 6. Democracy and the limits of punishment: a preface to prisoners' rights / Franklin E. Zimring and Gordon Hawkins -- 7. Prison reform amid the ruins of prisoners' rights / James B. Jacobs -- 8. Questioning the conventional wisdom of parole release authority / Kevin R. Reitz -- 9. The future of violence risk management / John Monahan